Associated Anomalies in Children With Cleft Lip And Palate in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Cleft lip and palate are the most frequent orofacial congenital defects that impact child health and survival. The incidence and types of cleft lip and palate vary across regions and countries. These children may potentially have associated anomalies that complicate their care and prognosis. The purpose of this study was to identify the associated anomalies linked to cleft lip and palate defects in Bangladeshi children.Materials and methods: This cross-sectional obser- vational study was conducted at Chittagong Medical College's Department of Anatomy between April 2021 and March 2022. A predesigned questionnaire was used to  gather socio-demographic data, cleft type, and the  existence of any associated anomalies from 100 children with cleft defects.Results: There were 58 males and 42 females among the 100 children. A cardiac abnormality was the most common (31%), followed by a mixed anomaly (25%), in which more than one aberration coexisted in a child with a cleft lip and palate. Skeletal, ocular, ear and CNS anomalies were among the others. Regarding related malformations, there was no significant difference between male and female offspring. The presence of associated anomalies had no significant relationship with the types of cleft deformity in the Chi-square test. An equal number of male and female children had associated anomalies. Children with isolated cleft palate had the highest percentage of anomalies (27.3%), followed by those with combined cleft lip and palate (17.2%).Conclusion: Before undergoing surgical repair, children with cleft lip and palate should have a thorough physical examination and necessary baseline investigations to rule out any associated anomalies. This would benefit their results of intervention and quality of life.JCMCTA 2023 ; 34 (2) : 107-110